Bio-physiological characteristics for juvenile coho salmon Oncorhynchus kisutch of artifcial and natural origin - L. L. Khovanskaya; E. A. Ryabukha (Известия ТИНРО, 2018)
Results of biological and physiological surveys of juvenile coho salmon from hatcheries of Magadan Region (artifcial origin) and from the main rivers of the northern Okhotsk Sea coast (natural origin) are presented. Biological and morpho-physiological indices of coho fry are compared between different salmon hatcheries and different rivers. Hematological indices for the fsh of natural origin are considered in dynamics. Positive effect of the higher water temperature and longer growing in artifcial conditions on length, body weight, fatness, feeding intensity and morpho-physiological indices of internal organs (liver, intestines) is detected for the coho fry; effect of the water temperature on length and weight of coho salmon in natural conditions is also positive. There is concluded that the coho salmon growing from the larvae under relatively high and stable temperature (4–5 oC) can provide the weight of fry over 0.6 g no later than middle July. If coho salmon is cultivated in conditions of low temperature (0.8–1.0 оС), the short-term growing before release (2.0–2.5 months) under a higher temperature (> 5o) is recommended to improve its fry quality, possibly in the nursery ponds equipped in natural reservoirs — in this case, the juveniles with the weight over 1.0 g could be produced in late August. Hematological indices are measured for different age groups of coho salmon from several rivers. Their dependence on the water temperature was not determined because of high variety of physiological state. However, a signifcant deviation to decrease from the normal values was detected for the red cell count and hemoglobin content in blood of the coho juveniles caught from the Taui River in 2018, obviously reasoned by their younger age and lower size and weight. The juveniles caught from the Yana River in 2016 had no signifcant deviations from the normal values, except of the hematocrit value that indicated stable conditions of their habitat and normal age structure. The hematological indices (hemoglobin content and red cell count) of coho juveniles caught from the Taui River in 2013 and 2014 corresponded to the end of downstream migration. Increasing of hematological indices with age of juveniles is found for coho salmon of natural origin living in favorable environments (favorable water temperature, good food supply).